1999
DOI: 10.1046/j.1525-1470.1999.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Pustular Folliculitis in Infancy: Report of Two New Cases

Abstract: Eosinophilic pustular folliculitis (EPF) is a cutaneous inflammatory follicular disorder of unknown etiology. The diagnosis is made on the basis of clinical and histopathologic features. We describe two patients who had recurrent episodes of pruritic follicular papular and pustular lesions on the face, extremities, and trunk. The eruptions lasted for 1 month with intermittent remissions. Laboratory tests disclosed no infectious or parasitic etiology in patient 2. In patient 1 we isolated methicillin-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 13 publications
0
25
1
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Twelve of the previously published cases were excluded, 13,20-27 some of which had already been questioned by other authors 28 : 1 atypical case on both clinical and histologic grounds (genital location exclusively, dermal infiltrate rich in neutrophils in 1 biopsy specimen, and in lymphocytes and macrophages in another) 25 ; 3 cases associated with immunodeficiency 26,27 ; 1 patient who developed sepsis with hepatic and pulmonary involvement in whom immunodeficiency was not ruled out 13 ; and 1 exceptional case in which the eruption did not recur, the histologic findings were inconclusive, and that was treated with granulocyte-colony stimulating factor (G-CSF) because of the extraordinarily high eosinophilia. 22 There were 6 more cases that were also excluded because of their atypical manifestations: a 4-year-old child who had recurrent vesicles and pustules along with erythema multiformeelike lesions on the abdomen and lower limbs that might have corresponded to arthropod bites 23 ; an 8-yearold boy with mucosal involvement, mixed dermal inflammatory infiltrate with eosinophils and neutrophils, and good response to dapsone in whom linear IgA was not excluded 20 ; an 11-year-old girl who presented with an isolated annular plaque on the cheek showing a dense eosinophilic infiltrate and necrotizing vasculitis of the small vessels, 24 which is not a feature of EPFI; a 5-year-old girl with ulcerated lesions on the lower legs that resolved in 2 weeks 21 ; and 2 more patients who presented with crops of pustular lesions on the trunk and lower limbs for 3 months' duration who demonstrated hypersensitivity to Dermatophagoides pteronyssinus and elevated IgE levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Twelve of the previously published cases were excluded, 13,20-27 some of which had already been questioned by other authors 28 : 1 atypical case on both clinical and histologic grounds (genital location exclusively, dermal infiltrate rich in neutrophils in 1 biopsy specimen, and in lymphocytes and macrophages in another) 25 ; 3 cases associated with immunodeficiency 26,27 ; 1 patient who developed sepsis with hepatic and pulmonary involvement in whom immunodeficiency was not ruled out 13 ; and 1 exceptional case in which the eruption did not recur, the histologic findings were inconclusive, and that was treated with granulocyte-colony stimulating factor (G-CSF) because of the extraordinarily high eosinophilia. 22 There were 6 more cases that were also excluded because of their atypical manifestations: a 4-year-old child who had recurrent vesicles and pustules along with erythema multiformeelike lesions on the abdomen and lower limbs that might have corresponded to arthropod bites 23 ; an 8-yearold boy with mucosal involvement, mixed dermal inflammatory infiltrate with eosinophils and neutrophils, and good response to dapsone in whom linear IgA was not excluded 20 ; an 11-year-old girl who presented with an isolated annular plaque on the cheek showing a dense eosinophilic infiltrate and necrotizing vasculitis of the small vessels, 24 which is not a feature of EPFI; a 5-year-old girl with ulcerated lesions on the lower legs that resolved in 2 weeks 21 ; and 2 more patients who presented with crops of pustular lesions on the trunk and lower limbs for 3 months' duration who demonstrated hypersensitivity to Dermatophagoides pteronyssinus and elevated IgE levels.…”
Section: Resultsmentioning
confidence: 99%
“…We agree with these authors that histologic findings for EPFI are not specific, in the sense that they cannot be considered pathognomonic, and that some of the published reports do not quite fit EPFI. 10,13,[20][21][22][23][24]26,27 However, after carefully reviewing the literature, we think that there are sufficient data favoring the existence of EPFI as a well-defined condition in infants that is different from the adult form of EPF.…”
Section: Resultsmentioning
confidence: 99%
“…243 More recently it has been suggested that the production of nitric oxide by eosinophils may have a pathogenetic role. [261][262][263][264] Onset can be as early as the first day of life. 231,[245][246][247][248][249][250][251][252][253] It differs from the classic form (Ofuji's disease) by the severe pruritus, the absence of circinate and palmoplantar lesions, and the less frequent involvement of the face.…”
Section: Acne Fulminansmentioning
confidence: 99%
“…To our knowledge, there are no case reports of a young child successfully treated with oral indomethacin, even though it is effective for adult cases. Oral antihistamine, erythromycin, 1 penicillin, dapsone, 2 tacrolimus ointment, 3 cyclosporine, 4 and topical indomethacin 5 have been reported to be useful in some childhood cases.…”
Section: Commentmentioning
confidence: 99%